FUNCTIONAL AND ANATOMICAL SIGNIFICANCE OF THE ECTOPIC INNER FOVEAL LAYERS IN EYES WITH IDIOPATHIC EPIRETINAL MEMBRANES: Surgical Results at 12 Months. Issue 2 (February 2019) - Govetto, Andrea; Virgili, Gianni; Rodriguez, Francisco J.; Figueroa, Marta S.; Sarraf, David; Hubschman, Jean Pierre
Abstract : Purpose: To describe the functional and anatomical outcomes of pars plana vitrectomy with epiretinal membrane and internal limiting membrane peel in eyes with and without ectopic inner foveal layers (EIFLs). Methods: In this retrospective multicenter study, patients diagnosed with idiopathic epiretinal membranes who underwent pars plana vitrectomy with epiretinal membrane and internal limiting membrane peel were enrolled, with a minimum follow-up of 12 months. Preoperative and postoperative spectral domain optical coherence tomography scans were qualitatively and quantitatively evaluated. The association of the EIFL and other spectral domain optical coherence tomography parameters with preoperative and postoperative best-corrected visual acuity (BCVA) was analyzed. Results: One hundred eleven eyes of 107 patients were included. Preoperatively, the EIFLs were present in 56 of 111 eyes (50.4%). The presence of EIFL was significantly associated with lower preoperative and postoperative BCVA ( P < 0.001). Ectopic inner foveal layer thickness was negatively correlated with preoperative BCVA (r = 0.58, P < 0.001). Postoperatively, the EIFL persisted in 51 of 56 eyes (91%) with Stage 3 and 4 epiretinal membranes. Ectopic inner foveal layer thickness decreased significantly after surgery ( P < 0.001), but postoperative EIFL thinning had no direct effect on postoperative change in BCVA. At 12 months from surgery, EIFL thickness maintained a significant negative correlation with BCVA (r = 0.55, P < 0.001). Conclusion: The presence of EIFL should be considered a negative prognostic factor for postoperative anatomical and functional recovery. Abstract : This study analyzed the outcomes of pars plana vitrectomy with epiretinal membrane peel in eyes with and without ectopic inner foveal layers. The presence of ectopic inner foveal layers was associated with lower preoperative and postoperative visual acuity and should be considered a negative prognostic factor for postoperative anatomical and functional recovery.